A tale of two worlds: the interstate system and world society in social science textbooks, 1950–2011. (8th August 2017) - Bromley, Patricia; Cole, Wade
ABSTRACT: There is a great and longstanding divide in visions of the international arena. Some assert that states are the most relevant actors in international politics, and others emphasise the importance of non-state actors as vehicles through which shared ideas and identities are enacted. Typically, cross-national scholarship adopts one of these positions and seeks to support the attendant theoretical claims; our approach is entirely different. We treat these varied conceptions of the international arena not as antecedent explanatory frameworks, but rather as outcomes to be explained in their own right. To this end, we draw on data consisting of 539 high-school social science textbooks (history, civics, social studies, and geography) from 73 countries published between 1950 and 2011, coded to shed light on how the international arena is discussed in national education systems. We use multilevel modelling to determine how characteristics of textbooks and countries are linked to different visions of the international arena. Stronger national emphases in books promote a vision of the interstate system, as does a country's level of democracy. Emphases on world society emerge particularly in recent decades and in books and countries most exposed to educational and social globalisation. Our findings provide initial support for arguments that world society and the interstate system are distinct, leading to multiple forms of inequality in the international arena.